Toxoplasma gondii e toxoplasmose. Bibliografia brasileira (1908-1974) - Giovannoni, Milton; Busetti, Eglé Therezinha; Costa, Márcia Lopes (Acta Biológica Paranaense, 1974)
Toxoplasma gondii e toxoplasmose. Bibliografia brasileira (1908-1974)